2021
DOI: 10.1002/hep4.1643
|View full text |Cite
|
Sign up to set email alerts
|

CMTM6 Stabilizes PD-L1 Expression and Is a New Prognostic Impact Factor in Hepatocellular Carcinoma

Abstract: CKLF-like MARVEL transmembrane domain containing 6 (CMTM6) was identified as a regulator of programmed death ligand 1 (PD-L1), which induces antitumor immunity in several cancers. This study aimed to clarify the relationship between CMTM6 and PD-L1 expression and clinical outcomes in patients with hepatocellular carcinoma (HCC). In total, 259 patients with HCC who had undergone hepatic resection were enrolled. Immunohistochemical staining for CMTM6 and PD-L1 was performed. The relationships between CMTM6 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The numbers of central intratumoral clusters of differentiation (CD) 8–positive lymphocytes and CD68‐positive macrophages with cytoplasmic or membrane staining in three high‐power fields were counted, as described previously. ( 9 , 13 ) The index of vessels that encapsulated tumor clusters (VETC) was calculated as reported previously. ( 9 , 14 ) Briefly, five representative fields were recorded for the total number of individual tumor clusters that were surrounded by endothelium, and the average number of endothelium‐coated tumor clusters per field is presented as the index of VETC.…”
Section: Methodsmentioning
confidence: 99%
“…The numbers of central intratumoral clusters of differentiation (CD) 8–positive lymphocytes and CD68‐positive macrophages with cytoplasmic or membrane staining in three high‐power fields were counted, as described previously. ( 9 , 13 ) The index of vessels that encapsulated tumor clusters (VETC) was calculated as reported previously. ( 9 , 14 ) Briefly, five representative fields were recorded for the total number of individual tumor clusters that were surrounded by endothelium, and the average number of endothelium‐coated tumor clusters per field is presented as the index of VETC.…”
Section: Methodsmentioning
confidence: 99%
“…As a key component of the TIME, TAMs play critical roles in its modulation, especially in tumor immune suppression [ 126 , 127 ]. TAMs are the most prominent immune cells in the vicinity of CAF-populated areas, suggesting tight interactions between these two cell types [ 128 ].…”
Section: Interaction Between Cafs and The Immune Microenvironment In Tumorsmentioning
confidence: 99%
“…Yugawa et al con rmed that CMTM6 and PD-L1 were coexpressed in HCC. They also found that high CMTM6 and PD-L1-positive expression was associated with malignant aggregates and shorter OS of HCC patients [44]. This may be due to its function in stabilizing PD-L1 expression, thereby facilitating escape from T-cell-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 92%